Anion receptors with glycoluril molecular scaffold - Kang, Jongmin; In, Sungjae; Cho, Seung Joo (TAYLOR & FRANCIS LTD, 2007)
For a synthetic receptor with an amide group, the amide groups are arranged through a space in a rigid and convergent manner. This has been achieved by incorporating amide groups into various molecular scaffolds. The geometry of diphenylglycoluril allows the synthesis of concave molecular structures. In addition, the rigidity of the molecule provides a solid molecular scaffold to arrange suitable binding moieties such as hydrogen bonds. We have developed various anion receptors based on diphenylglycoluril. The association of these receptors with various anions reflects the shape, size and basicity of the anions.
Keywords: RHENIUM(I) BIPYRIDYL; LIQUID-CRYSTALLINITY; BINDING-PROPERTIES; RECOGNITION; CLIPS; COORDINATION; CHEMISTRY; RUTHENIUM(II); COBALTOCENIUM; POLYROTAXANE